Pengaruh Information and Communication Technology (ICT) terhadap Pertumbuhan Ekonomi di Asean-4 - Adiet Try Waluyo; Dwi Hastuti Lestari Komarlina; Muhammad Nurhikmat; Asep Muhammad Adam (Ecoplan, 2026)
Information and Communication Technology (ICT) is one of the drivers of Sustainable Development (SDGs). This study examines the relationship between Information and Communication Technology (ICT), internet usage, and telephone ownership on income inequality in ASEAN-4, there is Indonesia, Malaysia, Philippines, and Myanmar using the Panel Vector Autoregressive Model (PVAR) approach from 2000 to 2022. Based on the test results, the ICT variable exhibits the largest influence on income inequality, accounting for 69%, then the internet usage and telephone ownership variables are 0.73% and 0.26%, respectively. This shows that ICT plays an important role in influencing per capita income in ASEAN-4 countries, namely Indonesia, Malaysia, the Philippines, and Myanmar.